Salmonella YrbD protein mediates invasion into the host by interacting with β2 integrin - Jun Cao; Jinliang Wang; Guanghui Dang; Shihao Ding; Yao Lu; Qiu Xu; Siguo Liu; Shenye Yu (Journal of Integrative Agriculture, 2025)
Salmonella enterica serovar Typhimurium, the causative agent of gastroenteritis, is one of the most successful intracellular pathogens. Although certain host factors for Salmonella infection have been unveiled, the factors mediating Salmonella entry, particularly the invasion process, remain obscure. Here, we have unearthed β2 integrin, a crucial member of the integrin family, as an important host factor facilitating Salmonella invasion. It is demonstrated that overexpression of β2 integrin promotes Salmonella invasion, while the knockdown of β2 integrin significantly diminishes the extent of invasion. Moreover, Salmonella exhibits specific binding affinity towards β2 integrin, and the block of β2 integrin on cell surface substantially reduces the infection of cells in vitro. The ectodomain soluble protein of β2 integrin neutralized Salmonella infection both in cells (in vitro) and in mice (in vivo). Additionally, Salmonella protein YrbD directly interacts with β2 integrin to facilitate its invasion. To our knowledge, this study showed for the first time that the protein YrbD mediates Salmonella adhesion and internalization into host cells by interacting with β2 integrin. These findings not only broaden our understanding of the mechanisms underlying Salmonella entry, but also identify a prospective target for therapeutic control.